Adoption and use of mobile banking by low‐income individuals in Senegal. Issue 2 (12th March 2020) - Fall, François Seck; Orozco, Luis; Akim, Al‐Mouksit
Abstract: The wide use of mobile phones increases low‐income individuals' access to a large range of services. One of these services is mobile banking (m‐banking). Today, m‐banking represents a key vector of financial inclusion in many countries in sub‐Saharan Africa, especially Senegal. Based on technology adoption theories applied to households in developing countries, this paper studies the determinants of the adoption and use of m‐banking. We distinguish between possession or adoption and actual use of m‐banking and examine the interdependence between these two decisions by using the Heckman sample selection model, through a sample of 1, 052 individuals in the suburbs of Dakar. Our main results are that the two decisions (adoption and use) are not independent of each other. Individual characteristics, such as education, possession of a bank account, and family network effects, are determinants of the adoption, and age, gender, and being a member of a tontine are determinants of the use. A major result of this study concerns women's low propensity to adopt m‐banking because of their low levels of education. However, compared with men, when women adopt m‐banking, they have a stronger propensity to use it.